Design, synthesis and biological evaluation of novel O-substituted tryptanthrin oxime derivatives as c-Jun N-terminal kinase inhibitors - Schepetkin, Igor A.; Kovrizhina, Anastasia R.; Stankevich, Ksenia S.; Khlebnikov, Andrei I.; Kirpotina, Liliya N.; Quinn, Mark T.; Cook, Matthew J. (Frontiers in Pharmacology, 2022)
The c-Jun N-terminal kinase (JNK) family includes three proteins (JNK1-3) that regulate many physiological processes, including inﬂammatory responses, morphogenesis, cell proliferation, differentiation, survival, and cell death. Therefore, JNK represents an attractive target for therapeutic intervention. Herein, a panel of novel tryptanthrin oxime analogs were synthesized and evaluated for JNK1-3 binding (Kd) and inhibition of cellular inflammatory responses (IC50). Several compounds exhibited submicromolar JNK binding affinity, with the most potent inhibitors being 6-(acetoxyimino)indolo[2,1-b]quinazolin-12(6H)-one (1j), which demonstrated high JNK1-3 binding affinity (Kd = 340, 490, and 180 nM for JNK1, JNK2, and JNK3, respectively) and inhibited lipopolysaccharide (LPS)-induced nuclear factor-κB/activating protein 1 (NF-κB/AP-1) transcription activity in THP-1Blue cells and interleukin-6 (IL-6) production in MonoMac-6 monocytic cells (IC50 = 0.8 and 1.7 µM, respectively). Compound 1j also inhibited LPS-induced production other proinflammatory cytokines, including IL-1α, IL-1β, granulocyte-macrophage colony-stimulating factor (GM-CSF), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor (TNF) in MonoMac-6 cells. Likewise, 1j inhibited LPS-induced c-Jun phosphorylation in MonoMac-6 cells, directly confirming JNK inhibition. Molecular modeling suggested modes of binding interaction of selected compounds in the JNK3 catalytic site that were in agreement with the experimental biological data on JNK3 binding. Our results demonstrate the potential for developing anti-inflammatory drugs based on these nitrogen-containing heterocyclic systems.